2010
DOI: 10.1007/s12038-010-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial activity of two natural alkaloids, vasicine acetate and 2-acetyl benzylamine, isolated from Indian shrub Adhatoda vasica Ness. leaves

Abstract: In folk medicine, Adhatoda vasica Ness. (Acanthaceae) is used to treat asthma and cough. The leaves of A. vasica were powdered and extracted with hexane, ethyl acetate and methanol. The hexane extract showed 97 percent reduction in colony-forming units (CFU) at 100 microg/ml. The hexane extract was subjected to column chromatography. Two natural compounds, vasicine acetate and 2-acetyl benzylamine, were isolated from it. They were bioassayed against Mycobacterium tuberculosis. The two compounds showed strong a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 15 publications
(15 reference statements)
0
26
0
Order By: Relevance
“…In our earlier communication, we have isolated 2-acetyl benzylamine from Adhatoda vasica leaves and investigated its antimycobacterial activity (Ignacimuthu and Shanmugam 2010). This resulted in the formation of N-benzyl-2,2,2-trifluoroacetamide as expected (Table 1; Fig.…”
Section: Resultsmentioning
confidence: 52%
“…In our earlier communication, we have isolated 2-acetyl benzylamine from Adhatoda vasica leaves and investigated its antimycobacterial activity (Ignacimuthu and Shanmugam 2010). This resulted in the formation of N-benzyl-2,2,2-trifluoroacetamide as expected (Table 1; Fig.…”
Section: Resultsmentioning
confidence: 52%
“…An open trial (Govindan et al, 1999(Govindan et al, , 2004 indicated that the Solanum trilobatum and Solanum virginianum had significantly lowered the parameters of asthma in mild-moderate asthmatic subjects. The effect of vasicine as bronchodilator (Atal, 1980), vasicine acetate and 2-acetylbenzyl amine as antimycobacterial (Ignacimuthu and Shanmugam, 2010) and an arabinogalactan as antitussive (Chattopadhyay et al, 2011) were reported previously. Zingiber officinale (Ahui et al, 2008), Ocimum tenuiflorum (Sridevi et al, 2009), Calotropis gigantea (Vadnere et al, 2010), Plectranthus amboinicus were reported previously for anti-inflammatory and mast cell stabilizing effect.…”
Section: Quantification Of the Datamentioning
confidence: 83%
“…Vasicine acetate was more effective than 2-acetyl benzylamine at all concentrations. [43] In support of above studies, Barry et al [44] and Gupta and Chopra [45] have also reported the antitubercular potential of AV.…”
Section: Antitubercular Activitymentioning
confidence: 73%